From Misogyny to Cult: An Etiological Reading of Genesis 3 - Danijel Berković (Kairos (English Ed.), 2009)
The complexity of issues involved in the history of women demands and deserves a wider and more detailed treatment than it has received till now. The aim of this article, which will limit itself to the religio-historical context, is to outline and highlight two extreme “positions” of women within the bipolar male-female world. The position of woman, her role and attitudes held about her, are predominantly determined by the Judeo-Christian tradition. This stance is, in turn, largely defined by the biblical account of the woman’s succumbing to the “snake” in Genesis 3. Since then, the woman has been marked as “weak” because it was she who succumbed to the “snake” and thus robbed humanity of a blissful existence in the Garden of Eden. In this way, the woman opened the door to the enemy of human souls as well as to the fallen fate of humankind. Nevertheless, the historical consequences of this biblical account on the position of women in society and family are not one-dimensional. On one hand, it brought about misogyny (hatred towards women), and on the other, an ongoing worship of the woman as the originator of human life exists in the form of the cult of fertility which is one of the most widespread religious expressions. As a syncretistic deviation, it also appears in the Old Testament text. In some Christian traditions, this cult appears as the counterpart to misogyny.